Analisis Akurasi Isi Materi Sirah Nabawiyah dalam Buku Ajar Sejarah Kebudayaan Islam (SKI) Kelas VII Madrasah Tsanawiyah - Selawati; Nani Triana (LPPM IAI PERSIS GARUT, 2025)
This study aims to analyze the conformity of the Sirah Nabawiyah content in the Islamic Cultural History (SKI) textbook for seventh-grade Madrasah Tsanawiyah (MTs) students with the classical reference Sirah Nabawiyah by Ibn Hisham. The research employs a qualitative descriptive approach using content analysis methods. Primary data were sourced from the 2020 edition of the Grade VII SKI textbook, while secondary data were drawn from volumes I and II of Sirah Ibn Hisham and other supporting literature. Findings indicate that out of 50 historical events analyzed, the majority of the facts presented in the textbook align with classical primary sources. However, some inconsistencies were found in chronology, data completeness, and additional narratives not found in the main reference. Furthermore, several popular materials used in the textbook lack clear citations. It is therefore recommended that the textbook be periodically revised based on authoritative literature and include proper documentation of sources to promote a more accurate and scholarly Islamic history education.